TEACHING ENGLISH FOR OIL AND GAS ENGINEERING STUDENTS: A PRACTITIONER’S PERSPECTIVE - Begmatov, Davron; teacher, ESL (Research Focus International Scientific Journal, 2026)
English for Specific Purposes (ESP) in the oil and gas sector demands far more than a standard language syllabus; it requires a deeply contextualized pedagogy rooted in professional practice, safety culture, and authentic communication. This article offers a reflective account of teaching English to undergraduate petroleum, drilling, and downstream process engineers. It argues that effective instruction begins with a rigorous needs analysis and continues through the deliberate teaching of polysemous technical vocabulary, the design of simulation- based activities, and the cultivation of assertiveness in hierarchical, multilingual work environments. By treating language not as an abstract system, but as a safety-critical professional tool, the teacher can transform passive engineering knowledge into active communicative competence. The discussion covers materials development from real drilling reports and incident investigations, task-based assessment aligned with industry procedures, and practical strategies for bridging the gap between high-level reading comprehension and productive speaking skills. The article concludes that teaching English to future oil and gas professionals is fundamentally an act of professional respect—one that equips students to think, speak, and act safely in the environments that power the world.